2002
DOI: 10.1177/153537020222700711
|View full text |Cite
|
Sign up to set email alerts
|

Serial Transplantation of p53-Deficient Hemopoietic Progenitor Cells to Assess Their Infinite Growth Potential

Abstract: Thirty-five years ago, Siminovitch et al. (Siminovitch L, Till JE, McCulloch EA. J Cell Com Physiol 64:23–32, 1964), using serially transplanted mouse spleens at 14-day intervals, observed a markedly progressive decline in the proliferative capacity of bone marrow (BM) cells, with the loss of cionogenicity by the fourth transplant generation. Using the same protocol, we assessed the proliferative capacity of p53-deficient mouse BM cells transplanted serially at the same 14-day intervals into lethally irradiate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 15 publications
2
13
0
Order By: Relevance
“…It would be reasonable to expect the HSC phenotype of the p53À/À animal to be similar to that of p21À/À. In fact, in the absence of p53, HSC function has been reported to be significantly enhanced under stress conditions (Wlodarski et al, 1998;Hirabayashi et al, 2002) in a manner opposite to that found in the absence of p21 during long-term engraftment. Since one of the major cellular functions of p53 is to initiate cell death upon genotoxic stress, the enhanced function of HSCs in the absence of p53 suggests that increased survival may predominate over the accelerated proliferation of HSCs in some settings.…”
Section: Roles Of Ckis In Stem Cell Regulationmentioning
confidence: 96%
“…It would be reasonable to expect the HSC phenotype of the p53À/À animal to be similar to that of p21À/À. In fact, in the absence of p53, HSC function has been reported to be significantly enhanced under stress conditions (Wlodarski et al, 1998;Hirabayashi et al, 2002) in a manner opposite to that found in the absence of p21 during long-term engraftment. Since one of the major cellular functions of p53 is to initiate cell death upon genotoxic stress, the enhanced function of HSCs in the absence of p53 suggests that increased survival may predominate over the accelerated proliferation of HSCs in some settings.…”
Section: Roles Of Ckis In Stem Cell Regulationmentioning
confidence: 96%
“…p53 family members are likely to play a major role in preventing the emergence of cancer stem cells. Indeed, reductions in p53 dosage have been shown to enhance stem cell division as well as other functional attributes (Palacios et al 1996;Shounan et al 1996;Hirabayashi et al 2002;TeKippe et al 2003;Dumble et al 2007). Most recently, two studies have shown that p53 deficiency in hematopoietic multipotent progenitor cells and neural stem/progenitor cells contribute to enhanced proliferative capacity of these cells (Akala et al 2008;Zheng et al 2008).…”
Section: Concluding Remarks: Insights and Hypotheses From Mouse Modelmentioning
confidence: 99%
“…23 We hypothesized that reduced HSC functionality drove the diminished regenerative ability in the blood of p53 ϩ/m mice and that the opposite may be true for the p53-deficient animals, which may have increased stem-cell functionality. Studies of HSCs from young p53 null mice showed that these cells are more robust in their self-renewal and reconstitution functions, [26][27][28][29] but the retention or loss of these properties in older p53-deficient HSCs has not been examined.…”
Section: Introductionmentioning
confidence: 99%